Case Report: Effect of a graded task-oriented throwing training on throwing accuracy and kinematic variability in a baseball player with the yips - Aoyama, T.; Uematsu, R.; Shibata, S.; Ae, K.; Kawamura, T.; Kohno, Y. (Frontiers in Sports and Active Living, 2025)
Despite the high prevalence of the yips, a task-specific movement disorder in athletes, effective exercise therapy remains elusive. This case report aimed to evaluate the impact of task-oriented training on throwing accuracy and kinematic variability in a baseball player with the yips. This study included a 21-year-old baseball player with a 7-year history of the yips. Approximately 50% of the player's typical throws were erratic and uncatchable. However, the frequency of erratic throwing varied depending on the throwing task and its contexts. To address these symptoms, graded task-oriented throwing training was implemented twice a week for 5 weeks. A three-dimensional motion capture system and high-speed camera were employed to assess throwing accuracy and kinematic variability. After the intervention, the frequency of subjective yips symptoms during throwing decreased by approximately one-third. Moreover, the intervention improved the accuracy of the ball arrival position and reduced variability in the ball release angle and shoulder internal rotation angle at ball release. Treating the yips remains challenging owing to concerns regarding doping and side effects. Nonetheless, this study suggests that low-risk physical therapy may have potential clinical utility as a management approach for athletes with the yips.